Amos Fortune, free man - Yates, Elizabeth; Unwin, Nora Spicer (New York, N.Y., U.S.A. : Puffin Books, 1989)
The life of the eighteenth-century African prince who, after being captured by slave traders, was brought to Massachusetts where he was a slave until he was able to buy his freedom at the age of sixty.
Reprint. Originally published: New York : Dutton, 1950.
Keywords: Fortune, Amos; Fortune, Amos; African Americans -- Massachusetts; Slaves -- Massachusetts; African Americans; Slaves